Analisis faktor keikutsertaan screening hepatitis “B” pada ibu hamil - Dedi Apriadi (Politeknik Kesehatan Kemenkes Aceh, 2021)
Background: Nagan Raya Regency is included in the top 5 districts/cities with the fourth highest number of hepatitis in Aceh Province. The hepatitis B screening program has not been implemented properly. The impact of the low coverage of this program affects public ignorance about the spread of hepatitis B from sufferers to other communities.Objective: This study aims to analyze the participation factors for Hepatitis B screening in pregnant women in the working area of the Ujong Patihah Health Center.Method: This research design is cross sectional study, in 2021. Data were collected using a questionnaire with a sample size of 220 pregnant women. Data collection was carried out by direct interviews with respondents, using a questionnaire instrument. Data analysis used the Cgi-square statistical test with a significance level of 95%, and continued with multivariate analysis using the Binary Logistics Regression test.Results: Bivariate analysis showed that there was a relationship between knowledge (p= 0.022), mother's attitude (p= 0.010), husband's role (p = 0.018), role of health workers (p = 0.028) and participation in hepatitis B screening, while education did not affect participation in hepatitis B screening (p= 0.668). Multivariate results showed that the mother's attitude was the dominant factor for participation in hepatitis B screening (OR= 2.24).Conclusion: Positive attitudes had a 2.24 times relationship to the participation of pregnant women in hepatitis B screening than negative attitudes.